Local Festival and Visitor Experience: Festival Innovation Design as an Attractive Regional Tourism Destination - I Nyoman Siryayasa; Sudarmi; Dharma Kuba (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study examines visitors' experiences of the Salo Karajae Festival, a local festival in Pare-pare City, South Sulawesi. It focuses on festival design innovations and the tourism experiences perceived by visitors. Data were collected through in-depth interviews with visitors, local governmen tofficials, organizers, and stakeholders. The analysis method used was a qualitative-interpretative approach. The results show that the Salo Karajae Festival has adopted various innovations in event design, particularly in response to the COVID-19 pandemic. Stringent health protocols were implemented to ensure visitor safety. At the same time, digital technology enhances engagement and accessibility to the festival, especially for Generation Z. Other innovations include diverse art performances, 3D landmarks, and virtual experiences. The research findings indicate that these innovations have successfully created captivating visitor festival experiences. The success of the Salo Karajae Festival in combining traditional elements with modern touches and the latest technology also enhances Pare-Pare City's image as an attractive tourist destination. This study enriches the literature on festival-based tourism and underscores the importance of innovation in enhancing tourist experiences. Practical implications include maintaining and improving festival innovation to sustain festival appeal and environmental sustainability. Future research is suggested to conduct more in-depth studies on festival sustainability and to test hypotheses between festival innovation design and visitor satisfaction quantitatively.